2009
DOI: 10.1002/ps.1756
|View full text |Cite
|
Sign up to set email alerts
|

Residual efficacy of pyriproxyfen and hydroprene applied to wood, metal and concrete for control of stored‐product insects

Abstract: Pyriproxyfen gave effective residual control of primary stored-product insect species by inhibiting adult emergence of exposed larvae. Results show that pyriproxyfen can be a useful addition for pest management programs in mills, warehouses and food storage facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 39 publications
1
27
0
7
Order By: Relevance
“…However, the activity of pyriproxyfen was found to be more potent than spinosad in Aedes aegypti (Darriet and Corbel 2006), Hydroprene in Tribolium confusum, T. castaneum, Oryzaephilus surinamenis, Lasioderma serricorne and Plodia interpunctella (Arthur et al 2009) while diofenolan was found to be more active than Lufenuron in Rhyncophorus ferrugineus (Ghoneim et al 2007). In the present study, both the compounds exerted equal or almost similar effects on S. liutra.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, the activity of pyriproxyfen was found to be more potent than spinosad in Aedes aegypti (Darriet and Corbel 2006), Hydroprene in Tribolium confusum, T. castaneum, Oryzaephilus surinamenis, Lasioderma serricorne and Plodia interpunctella (Arthur et al 2009) while diofenolan was found to be more active than Lufenuron in Rhyncophorus ferrugineus (Ghoneim et al 2007). In the present study, both the compounds exerted equal or almost similar effects on S. liutra.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies comparing the efficacy of pyriproxyfen with other IGRs like fenoxycarb and difubenzuron (Ross and Cochran 1991), chemical insecticides (Kerns and Stewart 2000), ecdysone agonist tebufenozide and neurotoxin spinosad (Medina et al 2003) with neurotoxin spinosad alone and in combination (Darriet and Corbel 2006) and IGR hydroprene (Arthur et al 2009) have been previously reported, but to best of our knowledge no comparative study of pyriproxyfen and diofenolan on the various stages of S. litura during the insect development has been reported. This prompted us to undertake the present study comparing the efficacy of two novel IGRs having JH mimic action on the polyphagous pest, S. litura.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For bulk-stored grain it is imperative that newly harvested commodities be stored in clean bins and not be loaded into bins that contain older products that may harbor insects. Harvesting equipment, transportation containers, loading areas, and storage bins need to be as clean as possible before harvest and storage of the new crop, and sometimes it is prudent to treat the surfaces of inside walls, floors, and ceilings of such structures and machinery with a residual insecticide to kill any insects that may remain following the previous storage season (7,92). Thus, mechanical, electrical, and structural engineering aspects of buildings and bins containing stored products must be considered during construction and maintenance of such structures.…”
Section: Value-added Food Productsmentioning
confidence: 99%
“…2). 나무 표면에 처리 시, bifenthrin은 처리 후 25일 까지 모든 발육단계 1령, 3령, 5령 약충 그리고 성충에서 (Watters et al, 1983;Arthur et al, 2009;Laskowski, 2002). (Fig.…”
Section: 서 론unclassified